Integrating Local Wisdom into Environmental Education: A Systematic Review of Ethnoscience Research in Indonesia - Sihombing, Rizky Agassy; Anwar, Sjaeful; Liu, Shiang-Yao; Muslim, Muslim; Winarno, Nanang; Sihombing, Putri Jessica (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
The erosion of environmental awareness and the diminishing recognition of traditional knowledge present significant challenges for contemporary education, particularly in Indonesia. This literature review examines the integration of ethnoscience into science education as a strategic response to these issues. Studies conducted between 2020 and 2025 reveal a growing emphasis on embedding local wisdom—such as indigenous agricultural practices and cultural rituals—into science curricula to enhance environmental consciousness and promote sustainable behaviors. A majority of the research focused on students, with senior high school (40%) and junior high school (26.7%) populations being the primary targets. Notably, research output surged in 2024, reflecting increasing academic interest. Ethnoscience-based instructional materials, including e-modules and interactive books, were widely implemented and demonstrated effectiveness in facilitating conceptual understanding while nurturing cultural appreciation. These tools were well-received by both educators and learners. Geographically, the studies spanned diverse regions, including Papua, Surabaya, and Ponorogo, underscoring the broad applicability of ethnoscience in Indonesian education. Although fewer studies concentrated on teachers, findings suggest that incorporating traditional knowledge into science education fosters cultural preservation, environmental stewardship, and sustainable development. This approach not only enriches the curriculum but also provides learners with a meaningful, context-driven educational experience rooted in both scientific inquiry and cultural heritage..Keywords: ethnoscience, environmental education, indonesia, systematic literature review, science learning